2018
DOI: 10.1002/cam4.1419
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine CFF‐1 induced cell growth inhibition, autophagy, and apoptosis via inhibiting EGFR‐related pathways in prostate cancer

Abstract: Traditional Chinese medicine (TCM) has a combined therapeutic result in cancer treatment by integrating holistic and local therapeutical effects, by which TCM can enhance the curative effect and reduce the side effect. In this study, we analyzed the effect of CFF‐1 (alcohol extract from an anticancer compound Chinese medicine) on prostate cancer (PCa) cell lines and studied in detail the mechanism of cell death induced by CFF‐1 in vitro and in vivo. From our data, we found for the first time that CFF‐1 obvious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 42 publications
(50 reference statements)
1
19
0
Order By: Relevance
“…A previous study demonstrated that the PI3K/Akt signaling pathway is inactivated, whereas osthole promotes the apoptosis of esophageal squamous cell carcinoma ( 48 ). Furthermore, repression of the PI3K/Akt signaling pathway inhibits cell viability and may enhance the apoptosis of PCa ( 49 ), indicating the role of the PI3K/Akt signaling pathway during tumor progression. Thus, the expression of PI3K and Akt was determined in the present study in order to explore the role of the PI3K/Akt pathway in the antitumor effect of si-ASF1B.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that the PI3K/Akt signaling pathway is inactivated, whereas osthole promotes the apoptosis of esophageal squamous cell carcinoma ( 48 ). Furthermore, repression of the PI3K/Akt signaling pathway inhibits cell viability and may enhance the apoptosis of PCa ( 49 ), indicating the role of the PI3K/Akt signaling pathway during tumor progression. Thus, the expression of PI3K and Akt was determined in the present study in order to explore the role of the PI3K/Akt pathway in the antitumor effect of si-ASF1B.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that antitumor drugs and related genes generally inhibit the growth of cancer cells and promote apoptosis. Proliferation and apoptosis are 2 important processes of tumor development [ 29 32 ]. Yang et al have confirmed that MTHFD1L silencing can repress viability of esophageal squamous cancer cells and expedite apoptosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although immunotherapy and targeted therapy are used in many tumors, these treatments are rarely used in VSCC patients at present. Some traditional Chinese medicines have been confirmed to be effective anti‐tumor agents (Song, Yang, Bai, & Ji, ; Wang, Zhao, Wu, Guan, & Wu, ; Wu et al, ). However, there have been no reports regarding the research on AS‐IV in VSCC.…”
Section: Discussionmentioning
confidence: 99%